DEGRADASI PERUSAHAAN PADA INDEKS LQ45 - Ayu Puspitaningtyas; Dhistianti Mei Rahmawan Tari (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
The purpose of this study is to analyze the degradation of companies in the LQ45 index. The population of this study is companies listed on the LQ45 index from February 2019 to July 2019. Total populations are 45 companies. The research sample used purposive sampling of 3 companies. The data is sourced from audited company financial statements downloaded from the Indonesia Stock Exchange website. The analytical method used is a horizontal analysis method that is comparing financial statements for several periods. The models studied are NOPLAT, FCF, ROIC, and CFI from DCF methods. Based on the NOPLAT analysis, all three companies were able to create net operational profits. Based on the FCF analysis, only PT Waskita Beton Precast Tbk. revenue’s that able to support its business development activities. Based on the ROIC and CFI analysis, only PT Elnusa Tbk. tended to be stable in providing funds to pay debtholders and stakeholders.